LIMITASI LIVING LAW SEBAGAI ASAS LEGALITAS MATERIL DALAM PEMBARUAN HUKUM PIDANA - Purwandiny, Dessy Adhya; Jullyan, Rendy Erianto; Satriawan, Arnezul Achmad; Malie, Adi Muliawansyah (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
The reform of criminal law constitutes an unavoidable response to the dynamic development of societal values and demands for justice. The enactment of the New Criminal Code, particularly the recognition of living law in Article 2, has generated fundamental debate concerning its implications for the principle of legality. This article aims to examine the philosophical and normative foundations of the inclusion of living law and to critically analyze the appropriate limitations of living law as a manifestation of material legality within the framework of criminal law reform. This study employs normative legal research using a statutory approach and a conceptual approach. The analysis of Article 2 of the New Criminal Code is conducted through systematic interpretation, by positioning the living law clause within the overall structure of the criminal law system, and teleological interpretation, by examining its objectives in balancing justice and legal certainty. The study is grounded in legal positivism and the doctrine of legal certainty as its primary theoretical analytical tools to assess the coherence of living law with the fundamental principles of legality, particularly lex certa, lex stricta, and lex scripta. The findings indicate that the principle of legality in the New Criminal Code is formulated in a material sense by acknowledging legal values that live and develop within society, in line with Article 28 of the Law on Judicial Power, which obliges judges to explore and understand the living values of law and justice. Nevertheless, the recognition of living law without clear normative boundaries poses a potential risk to legal certainty and predictability in criminal law enforcement. Therefore, this article argues that living law must be strictly limited through formal regulation at the provincial level, as mandated by Article 2 of the New Criminal Code. Such limitations are essential to ensure the protection of customary law maintained by Indigenous Communities while simultaneously safeguarding the principle of legality as the core foundation of criminal law.